The Concept of Education According to John Dewey and Cornelius Van Til and Its Implications in The Design of Early Childhood Character Curriculum - Thinna Naftali Woenardi; Haris Supratno; Mudjito Mudjito; Irlen Olshenia Rambu Putri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This research discusses a comparative study between the educational concepts of John Dewey and Cornelius Van Til to find a concept of education that teaches children not only to achieve intellectual intelligence but also to shape the child's character and make the child a person who fears God. This research uses a qualitative method, a literature study research approach (library). Based on the results of the research, the author makes a curriculum design that tends to Van Til's concept of education because in the idea of education according to Van Til, he emphasizes education based on God's Word, which is the basis for building human character and making children as individuals who are not only intellectually intelligent but also intellectually intelligent. The results of this research indicate that there is a sharp difference between the views of John Dewey and Cornelius Van Til regarding education. John Dewey focused education on human intelligence alone. Education must introduce children to who their Creator is so that children live responsibly towards their Creator. Education that intervenes in faith, education that applies Bible integration teaches children moral values ​​and character to become God-fearing individual’s fear of God.